2011
DOI: 10.1182/blood.v118.21.283.283
|View full text |Cite
|
Sign up to set email alerts
|

Mutations of NOTCH1 Are An Independent Predictor of Survival in Chronic Lymphocytic Leukemia

Abstract: 283 The clinical course of chronic lymphocytic leukemia (CLL) ranges from very indolent, with a nearly normal life expectancy, to rapidly progressive leading to death and occasionally undergoing transformation to Richter syndrome (RS). TP53 disruption identifies a fraction of high risk CLL destined to experience a very short survival. High risk CLL, however, cannot be fully recapitulated by TP53 disruption and other lesions of cancer genes may be implicated in this aggressive phenotype. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
126
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(146 citation statements)
references
References 0 publications
13
126
2
5
Order By: Relevance
“…It is plausible that different times of sample collection from untreated patients was one of the major reasons to explain these discrepancies. The relationship among molecular alterations in our study was mostly consistent with the reported data, including that NOTCH1 mutations occurred exclusively without TP53 mutations (Rossi et al , ) and un‐mutated IGHV was frequently associated with SF3B1 mutations (Xia et al , ). However, more IGHV ‐mutated patients in our cohort had ZAP70 expression compared with that of reported data (Wiestner et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…It is plausible that different times of sample collection from untreated patients was one of the major reasons to explain these discrepancies. The relationship among molecular alterations in our study was mostly consistent with the reported data, including that NOTCH1 mutations occurred exclusively without TP53 mutations (Rossi et al , ) and un‐mutated IGHV was frequently associated with SF3B1 mutations (Xia et al , ). However, more IGHV ‐mutated patients in our cohort had ZAP70 expression compared with that of reported data (Wiestner et al , ).…”
Section: Discussionsupporting
confidence: 91%
“…We do not confirm the reported specific association of subset #1 with del(17p) , although this aberration was present in almost one‐third of cases. The evaluation of the recently identified gene mutations did not show a specific enrichment in NOTCH1 (15%) or BIRC3 mutations (5%) among subset #1 CLL, who presented a prevalence similar to what reported among UM CLL at diagnosis . No SF3B1 mutation was identified.…”
Section: Discussionmentioning
confidence: 49%
“…All mutations identified in WGA were confirmed using the corresponding gDNA. PCR primers and conditions have been previously described . As BIRC3 might be affected also by deletions, FISH analysis using the RP11‐177O8 probe was performed, as described .…”
Section: Methodsmentioning
confidence: 99%
“…Relapsed/refractory CLL patients consecutively treated with alemtuzumab between 2003 and 2013 were identified in the institutional database, and baseline clinical data, treatment modalities, efficacy, safety and disease course were extracted. Tumor samples collected before treatment start were assessed for FISH karyotyping, expression of ZAP‐70, CD38, and CD49d, mutational status of the IGHV, TP53, NOTCH1, SF3B1, and BIRC3 genes .…”
Section: Methodsmentioning
confidence: 99%